Copper-induced aggregation of IgG: a potential driving force for the formation of circulating protein aggregates - Saporito Magriñá, Christian Martín (2023)
Copper is a highly reactive element involved in a myriad of biological reactions. Thus, while essential for mammalian cells, its concentrations must be kept in check in order to avoid toxicity. This metal participates in redox reactions and may exacerbate oxidative stress in aerobic organisms. Nonetheless, the actual driving force of copper-induced cell death is yet unknown. Likely, free copper ions may target different biomolecules that are crucial for the proper functioning of an organism. In this work, we show that free copper induces protein aggregation in serum. The wide set of proteins present in these biological samples are not equally prone to copper-induced aggregation and some, such as albumin, are highly resistant, whereas γ-globulins are highly sensitive. The identity of the proteins in the aggregates becomes fairly homogeneous as metal concentrations go as low as 20 μM. The identification of the proteins by mass spectrometry indicates a preponderance of IgG and a minor presence of other different proteins. Therefore, free copper in blood may contribute to the formation of circulating protein aggregates with a core of IgG. This may impact health not only due to the activity of aggregated IgG but also due to the many proteins co-aggregated. Understanding whether the γ-globulin core and the heterogeneous subgroup of proteins elicit differential responses in the organisms requires further research.